Effect of a school soccer competition with consecutive day games on the recovery status of U-19 players - Suene Franciele Nunes Chaves; Matheus Santos Cerqueira; Guilherme Tucher; Bernardo Miloski; Daniel Barbosa Coelho; Diego de Alcantara Borba; Pedro M.Q. Pimenta; João B. Ferreira-Júnior (Universidade Federal de Santa Catarina, 2018)
The present study aimed to evaluate the effect of a school soccer competition with consecutive day games on the recovery status of U-19 players. Thirty-one school athletes (17.1±1.1 years) who played a U-19 school soccer competition (composed of two groups of four soccer teams each, followed by semifinals and final) were randomly evaluated. Games lasted 70 min (two periods of 35 min with 15 min rest interval), and they were played on consecutive days with 24 h between each game. Delayed onset muscle soreness (DOMS) and Total Quality Recovery (TQR) were measured before group phase games (n= 31) and semifinals games (n= 18). The internal game load was measured by the session rate of perceived exertion (session-RPE) method. TQR was higher before the first game when compared to the other games (p< 0.001). DOMS increased after the first game and did not return to baseline before the fourth game. Both session-RPE and internal load of the fourth game were higher than in the other games (p< 0.001). In addition, there was no correlation between internal game load and TQR (p> 0.05). The monotony observed during the evaluated period was 3.1±2.0 AU. The results indicate that the 24 h rest period seems to be insufficient for complete recovery of U-19 soccer school athletes, suggesting the organization of U-19 school soccer competitions with higher rest interval between games and search for methods to increase the recovery rate.